Water in Alkali Aluminosilicate Glasses - Balzer, Robert; Behrens, Harald; Waurischk, Tina; Reinsch, Stefan; Müller, Ralf; Kiefer, Philipe; Deubener, Joachim; Fechtelkord, Michael (Frontiers in Materials, 2020)
To understand the influence of water and alkalis on aluminosilicate glasses, three polymerized glasses with varying ratios of Na/K were synthesized [(22. 5-x)Na2O-xK2O-22.5 Al2O3-55 SiO2 with x = 0, 7.5, and 11.25]. Subsequently, these glasses were hydrated (up to 8 wt% H2O) in an internally heated gas pressure vessel. The density of hydrous glasses linearly decreased with water content above 1 wt%, consistent with the partial molar volume of H2O of 12 cm3/mol. Near-infrared spectroscopy revealed that hydroxyl groups are the dominant species at water content of <4 wt%, and molecular water becomes dominating at water content of >5 wt%. The fraction of OH is particularly high in the pure Na-bearing glass compared to the mixed alkali glasses. 27Al magic angle spinning-NMR spectroscopy shows that aluminum is exclusively fourfold coordinated with some variations in the local geometry. It appears that the local structure around Al becomes more ordered with increasing K/Na ratio. The incorporation of H2O reinforces this effect. The differential thermal analysis of hydrous glasses shows a significant mass loss in the range of glass transition already during the first upscan, implying the high mobility of water in the glasses. This observation can be explained by the open structure of the aluminosilicate network and by the low dissociation enthalpy of H2O in the glasses (≈ 8 kJ/mol). The effect of the dissolved H2O on the glass transition temperature is less pronounced than for other aluminosilicate glasses, probably because of the large fraction of Al in the glasses.